2014
DOI: 10.1109/tps.2014.2330840
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characteristics of Supersonically Expanding Nitrogen Arc-Jet Plume—Strong Atomic Lines and Weak Molecular Band Spectra

Abstract: We generate recombining nitrogen plasma plume by expansion of nitrogen arc into lower pressure vessel with a weak longitudinal magnetic field in a steady state. Spectroscopic observation reveals that the plasma has almost no component of molecular band spectra. Meanwhile, atomic nitrogen lines are observed with considerable intensity. The reason for this spectroscopic peculiarity is discussed in terms of chemical thermodynamics of the nitrogen thermal arc plasma and of nonequilibrium characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…[25][26][27] Furthermore, emission of N atoms was also observed at wavelengths λ = 742, 744 and 746 nm. 18,27) It should be remarked that the argon lines cannot be observed with sufficient intensity in Figs. 3(b)-3(c), which is considered to be rapid collisional quenching of argon excited states with N 2 molecules.…”
Section: Oes Measurement Systemmentioning
confidence: 96%
See 1 more Smart Citation
“…[25][26][27] Furthermore, emission of N atoms was also observed at wavelengths λ = 742, 744 and 746 nm. 18,27) It should be remarked that the argon lines cannot be observed with sufficient intensity in Figs. 3(b)-3(c), which is considered to be rapid collisional quenching of argon excited states with N 2 molecules.…”
Section: Oes Measurement Systemmentioning
confidence: 96%
“…It should be also noted that the plasma parameter of the argon plasma without gas puff was already examined in the previous study with this discharge apparatus under the similar condition. [16][17][18] The electron temperature T e on the plasma jet axis was found to be T e ∼ 0.8-1.0 eV at Z ∼ 30 mm, T e ∼ 0.5-0.7 eV at Z ∼ 100 mm, and T e ∼ 0.3-0.4 eV at Z ⩾ 170 mm, where Z is the longitudinal distance measured from the anode nozzle. Meanwhile, the electron density N e was found to be N e ∼ 10 13 -10 14 cm −3 at Z ⩽ 100 mm, N e ∼ 10 12 -10 13 cm −3 at Z ∼ 200 mm, and N e ∼ 10 11 -10 12 cm −3 at Z ∼ 300 mm.…”
Section: Experimental Equipmentmentioning
confidence: 99%
“…Akatsuka et al reported the generated N atom density is 10 24 m −3 maximum at the arc discharge region. The loss of nitrogen atoms to the wall is small because of supersonic arc-jet [11]. Ichiki et al reported about a new nitriding method in which pulsed-arc plasma jet with N and hydrogen mixture gas is used.…”
Section: Introductionmentioning
confidence: 99%